Studi Literature: Analisis Pengaruh Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha Siswa SMK - Teguh Wijaksana Isma; M Giatman; E Nazar (STKIP PGRI SITUBONDO, 2021)
Entrepreneurship is one way that can be done to reduce unemployment in Indonesia. However, the low interest in entrepreneurship, especially vocational students is one of the problems experienced now. Several factors cause vocational students to be less interested in entrepreneurship, one of which is the lack of knowledge of vocational students about entrepreneurial knowledge. The purpose of this study was to analyze the effect of entrepreneurial knowledge on entrepreneurial interest in vocational students. The type of research conducted is a literature study. Data is collected by searching for references on the internet. From the search that has been carried out, 21 references have been obtained that are in accordance with what you want to study, namely about the influence of entrepreneurial knowledge on the entrepreneurial interest of vocational students. Based on the results of the literature study that has been carried out, from 21 references obtained 18 references concluded that there was an influence of entrepreneurial knowledge or 85.71% while 3 references concluded that there was no influence of entrepreneurial knowledge or 14.29%. So it can be concluded that entrepreneurial knowledge has an effect on the entrepreneurial interest of SMK students.